Situation Report: Poland, 14 November 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Polish Government Presents Economic Program / by Louisa Vinton Government Spokesman Present Foreign Policy Aims / by Anna Swidlicka A New Departure in Polish-Soviet Relations / by Anna Swidlicka Gazeta Wyborcza on the German Minority in Poland / by Anna Swidlicka Government Pledges to Treat All Political Groups Equally / by Anna Swidlicka Poland Plans Convertible Zloty / by Vladimir Sobell Private Education: Poland's Growth Industry? / by Roman Stefanowski